Authority, continuity, and change in Islamic law - Hallaq, Wael B., 1955- (Cambridge University Press, 2001)
In his latest book, Wael Hallaq examines the relationship between authority, continuity and change in Islamic law and concludes that the mechanisms of change are embedded in its very structure despite its inherent conservatism. Scholars will welcome the intellectual rigor and innovation of this pathbreaking analysis.